2017
DOI: 10.1002/cncr.31136
|View full text |Cite
|
Sign up to set email alerts
|

A mutational comparison of adult and adolescent and young adult (AYA) colon cancer

Abstract: The current results provide the rationale for a more comprehensive study with a larger sample set and experimental validation of the functional impact of the identified variants along with their contribution to the biologic and clinical characteristics of AYA colon cancer. Cancer 2018;124:1070-82. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 37 publications
0
43
0
Order By: Relevance
“…11 These data may help to stimulate future trial proposals to investigate the possibility of the exclusion or selective use of adjuvant therapies for stage II and III disease in the younger cohort to help to decrease treatment toxicity. Moreover, progressive age within this younger cohort is not a significant determinant of survival or a response to adjuvant therapies.…”
Section: Discussionmentioning
confidence: 99%
“…11 These data may help to stimulate future trial proposals to investigate the possibility of the exclusion or selective use of adjuvant therapies for stage II and III disease in the younger cohort to help to decrease treatment toxicity. Moreover, progressive age within this younger cohort is not a significant determinant of survival or a response to adjuvant therapies.…”
Section: Discussionmentioning
confidence: 99%
“…AYA cancers have unique biological/genomic characteristics, and analysis of driver mutations in AYA cancer is a new but growing field of research . In breast and colorectal cancer, the mutational burden of AYA cancers appears to be higher, and less favorable histology, such as mucinous colon cancer or triple‐negative breast cancer, is overrepresented in the adolescent population . In colorectal cancer, mismatch repair genes appear to be disproportionately affected in AYA patients compared with older adults, even excluding patients with the genetic predisposition hereditary nonpolyposis colon cancer syndrome (Lynch syndrome), and mutations in the MUC gene seem to be correlated with the higher incidence of mucinous colorectal cancer .…”
Section: Biologic Features Of Aya Cancer Typesmentioning
confidence: 99%
“…9,10 In colorectal cancer, mismatch re pair genes appear to be disproportionately affected in AYA patients compared with older adults, even excluding patients with the genetic predisposition hereditary nonpolyposis colon cancer syndrome (Lynch syndrome), and mutations in the MUC gene seem to be correlated with the higher in cidence of mucinous colorectal cancer. 9 In addition, recent studies have suggested that the rising incidence of colorectal cancer in young adults may be related to the parallel increase in obesity. 23 In melanoma, mutations associated with sun ex posure are present at similar rates in AYAs and older adults, but AYAs have a different distribution of nonultraviolet associated DNA damage, potentially linked to mismatch gene repair, which may contribute to AYA melanoma de velopement.…”
Section: Biologic Features Of Aya Cancer Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…In mature neurons, PHR proteins take on an important role in axon degeneration following injury (27,28). Outside of the nervous system, PHR proteins are implicated in oncogenesis (29)(30)(31)(32)(33)(34). Despite growing recognition of the functional importance of PHR proteins, relatively little is known about how components of atypical PHR ubiquitin ligase complexes assemble.…”
mentioning
confidence: 99%